Tantangan Geopolitik Kerja Sama Indonesia China dalam Proyek Pembangunan Kereta Cepat Jakarta-Bandung - Riandharu Ari Pratista; Aditya Ferdana Putra; Wahyu Purnomo (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The Jakarta-Bandung High Speed Rail (KCJB) project is one of the strategic infrastructure initiatives resulting from the output of cooperation between Indonesia and China following the Belt and Road Initiative (BRI) policy. Although the project is promising in improving transportation efficiency, reducing carbon emissions, and the potential for regional economic growth, its implementation is inseparable from various challenges, one of which is geopolitics. This research aims to find out the geopolitical dynamics that arise due to China's incentives in financing and mastering KCJB technology, and also examine Indonesia's position in the midst of regional conflicts, one of which is the South China Sea dispute. The method in this research is qualitative based on literature study. This research reveals that the KCJB project is not just technical cooperation, but reflects a struggle for strategic influence. Indonesia's dependence on financing and technology from China creates potential asymmetry in bilateral relations and risks to sovereignty. The findings are expected to enrich the discourse on foreign policy and national infrastructure in the face of increasingly complex regional or global challenges.